2012
DOI: 10.1021/ma3020195
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Responsive Polymer Brushes Grafted from Polystyrene Nanoparticles by Means of Surface Initiated Atom Transfer Radical Polymerization

Abstract: Well-defined poly(2-(methacryloyloxy)ethyl ferrocenecarboxylate) (PFcMA) brushes were synthesized by surface-initiated atom transfer radical polymerization (SI-ATRP) on cross-linked polystyrene particles. The ATRP of FcMA monomer was reinvestigated leading to molar masses up to 130 kg mol–1 with a good reaction control and high monomer conversion (91%). The SI-ATRP was done with different amounts of initiator in the PS particle shell leading to PFcMA surface conformations from “mushroom-like” to dense “brush-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 72 publications
7
126
0
Order By: Relevance
“…2-(methacryloyloxy)ethyl ferrocenecarboxylate (FcMA) monomer 1 was synthesized described elsewhere. [ 51 ] Triethoxy functionalized polyvinylferrocenes (PVFc-TEOS) were synthesized via anionic polymerization as recently reported. [ 49 ] Instrumentation : Standard SEC was performed with tetrahydrofuran (THF) as the mobile phase (fl ow rate 1 mL min −1 ) on a SDV column set from PSS (SDV 1000, SDV 100000, SDV 1000000) at 30 ° C. Calibration was carried out using PS standards (from Polymer Standard Service, Mainz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-(methacryloyloxy)ethyl ferrocenecarboxylate (FcMA) monomer 1 was synthesized described elsewhere. [ 51 ] Triethoxy functionalized polyvinylferrocenes (PVFc-TEOS) were synthesized via anionic polymerization as recently reported. [ 49 ] Instrumentation : Standard SEC was performed with tetrahydrofuran (THF) as the mobile phase (fl ow rate 1 mL min −1 ) on a SDV column set from PSS (SDV 1000, SDV 100000, SDV 1000000) at 30 ° C. Calibration was carried out using PS standards (from Polymer Standard Service, Mainz).…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that molar masses for surface-attached PFcMA and PFcMA chains obtained by ATRP in solution were in a comparable range. [ 51 ] All SEC results for the samples used are compiled in Table 2 . The presence of polymer in the PFcMA-modifi ed mesoporous samples was monitored by infrared spectroscopy ( Figure 3 ) and corroborated by XRR.…”
Section: Mesoporous Silica and Polymer Modifi Cationmentioning
confidence: 99%
“…The shell of the particles was treated with divinylbenzene (DVB) as cross-linker and an atom transfer radical polymerization (ATRP) initiator, which additionally acts as a monomer (also referred to as ATRP-inimer) for the intended surface-initiated atom transfer radical polymerization (SI-ATRP) of protonated styrene monomer (see Fig. 2) (13). SI-ATRP of styrene was carried out to generate grafted PS chains with molar masses up to 50 kg mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Those particles were used because of their simple synthesis via seeded emulsion polymerization, similar to a previously described procedure, leading to almost monodisperse particles [57]. For further purification, the particles were dried by three-fold azeotropic distillation with dry toluene under high vacuum conditions.…”
Section: Surface-initiated Anionic Polymerization Of Dmsb On Cross-limentioning
confidence: 99%